Perspectives of Adolescents, Parents, Service Providers, and Teachers on Mobile Phone Use for Sexual Reproductive Health Education - Beverly M. Ochieng; Lesley Smith; Bev Orton; Mark Hayter; Margaret Kaseje; Charles O. Wafula; Penina Ocholla; Franklin Onukwugha; Dan C. O. Kaseje (Social Sciences, 2022)
Mobile health (mHealth) programs offer opportunities to improve the sexual and reproductive health (SRH) of adolescents by providing information. This paper reports the findings of a study carried out in Homabay County, Kenya, to assess stakeholders’ perspectives on access to and use of mobile phones by adolescents for SRH education. We aimed to establish whether mobile phones could facilitate access to SRH information by adolescents and the barriers to be addressed. This was a qualitative exploratory study involving adolescents, parents, teachers, health care workers, and community health volunteers. Data were collected through focus group discussions (FGDs) and key informant interviews (KIIs), and were analyzed through thematic and content analysis. Respondents lauded mHealth as an effective and efficient approach to adolescent SRH education with a potential to promote the learning of useful SRH information to influence their behavior formation. Respondents pointed out bottlenecks such as the limited ownership of and inequitable access to phones among adolescents, logistical barriers such as lack of electricity, internet connectivity, and the impact of phones on school performance, which must be addressed. The usefulness of mHealth in adolescent SRH education can be enhanced through inclusive program formulation and co-creation, implemented through safe spaces where adolescents would access information in groups, and supported by trained counselors.